Beguiled by beauty: cultivating a life of contemplation and compassion - Farley, Wendy (Westminster John Knox Press, 2020)
1.Contemplation on the borderlands --2.We are made for the Beloved --3.Awakening to beauty --4.Practice --5.Contemplative dispositions --6.Watching the mind --7.Guarding the heart --8.Contemplative practices.